JULGAMENTO PELOS GESTORES DOS ESTEREÓTIPOS DO CONTADOR DIANTE DOS PRINCÍPIOS GLOBAIS DE CONTABILIDADE GERENCIAL - EUMIR DE MORAES RONDON (2023)
In the business environment, the importance of maintaining a reliable professional image becomes relevant for relationships of trust in the flow of information in which the accountant reflects the results of his work, which should add to the relevance of managerial decisionmaking. Previous studies on the accountant stereotype present positive stereotyping results, but with negative traits centered on the bureaucratic image. When considering the development of accounting in light of the Global Management Accounting Principles (PGCG) adhered to the quality parameters, guidelines and attributes of management accounting, the accountant becomes capable of adding value to the information made available to internal and external clients, supporting the organizations in better decision making, and thus improving the accountant's image in the eyes of managers. The objective of this research was to evaluate the judgment by managers of the stereotypes of accounting professionals in light of the Global Management Accounting Principles. The use of the experimental method through a 2 x 2 factorial configuration (simulation of the absence and presence of PGCG between accountants) forming four scenarios allowing to identify the behavior of managers in the face of the experimental treatments used, also investigating the issue of sex (female/ male) in the accounting profession. The sample was reached with a minimum of 20 participants per group, with professionals working in business areas, with a total of 101 voluntary participants, composing valid results. The instrument made available through a link on the Qualtrics® online platform allowed its random distribution among respondents, guaranteeing the internal validity of the instrument. The statistical analyzes carried out for the four hypotheses, through the Sdudent t Test and the ANOVA test with Post Hoc Tukey analysis, allowed us to infer that accounting professionals are positively stereotyped by managers when they practice the Global Management Accounting Principles. There is a difference in stereotyping between the accountant and the accountant related to the leadership situation, however, when both practice PGCG, no difference was statistically identified across the situations analyzed. Another result shows that managers have greater conviction in using the information produced by the accounting professional when he prepares the accounting information in light of the PGCG. For new research, an expansion of the sample is recommended, with the purpose of understanding the behavior of managers by region of the country and predominant cultures, associating the results with the manager's profile, personality traits, taking into account how these Personal characteristics can interfere with the manager's behavior in stereotyping accountants.